Topsy and Tim: Learn to Swim - Jean and Great Adamson (Ladybird London)
Going to the swimming pool for the first time can be daunting but Topsy and Tim are having fun! Follow the twins on their adventures as they have lessons, learn to swim without their armbands and take part in a swimming competition.
3-5
Keywords: Language